(untitled) (Medical Forum Monthly, 2024)
Objective: To assess and analyze the potential association between blood groups and fingerprint patterns. Study Design: Descriptive Cross-sectional Study Place and Duration of Study: This study was conducted at the Forensic Medicine & Toxicology Department of Sahara Medical College Narowal, Punjab-Pakistan from July 2020 to June 2023. Methods: A sample of 293 participants was meticulously studied, categorizing individuals based on their blood groups and assessing their respective fingerprint patterns. This research delves into the intriguing relationship between blood groups and fingerprint patterns, shedding light on potential associations that could have far-reaching implications. Results: The findings are presented in a comprehensive cross tabulation analysis, revealing a statistically significant association between blood groups and fingerprint patterns (p = 0.013). Particularly, the blood group of an individual appears to influence the distribution of their fingerprint pattern. Conclusion: These results provide a promising foundation for further exploration of the mechanisms underlying this association and its potential applications in fields such as forensics and medical diagnostics. This study marks a crucial step towards understanding the intricate interplay between genetic factors and biometric features, opening new avenues for research and practical applications.